Is there a role for endothelial dysfunction in the pathogenesis of lumbar disc degeneration? A hypothesis that needs to be tested. Issue 3 (March 2015) - Papalia, Rocco; Albo, Erika; Vadalà, Gianluca; D'Adamio, Stefano; Lanotte, Angela; Di Martino, Alberto; Denaro, Vincenzo
Abstract Low back pain is a painful condition affecting most people at least once in their life. It can be the expression of lumbar disc degeneration, a condition whose progression is influenced by environmental, individual and genetic factors. The pathogenesis of this condition implies the reduction of sustenance for the tissues within the intervertebral disc (ID) due to a decreased blood flow in the local microcirculation. In fact, it is known that the ID is an avascular structure that receives nutritive molecules and exchanges waste products through a process of osmotic diffusion from the capillaries located at the ID–vertebral body interface. The maintenance of a correct oxygen supply is essential for the health of disc cells also because ID is subjected to continuous compression stress due to its bearing function between vertebral bodies. This vital condition is guaranteed by proper dilation of blood vessels in response to mechanical stress, thanks to a finely balanced homeostasis between vasodilatory factors, such as nitric oxide, and vasoconstrictive substances produced by the endothelium. Endothelial dysfunction may disrupt this delicate equilibrium, causing a reduced oxygen supply eventually resulting in ID degeneration. Our hypothesis is that endothelial dysfunction, a systemic condition of reduced vessel dilation in response to mechanical stress, should be considered as an important pathological factor implicated intervertebral disc degeneration. This relationship may pave the way for a change in therapeutic approach to low back pain, especially in the early stages.